Efficiency of a wind plant in real conditions with additional costs and the market price of electricity - Pokrovskiy, K. (Energy and Automation, 2023)
In its development, the global energy sector is constantly demonstrating the growth of electricity consumption. Traditional power plants in this process ensure an increase in greenhouse emissions and aggravation of climate problems, which are becoming more relevant every year. Against this background, modern alternative energy sources, namely wind power plants, contribute to reducing the impact of traditional power plants and encourage solving environmental problems. The development of global wind energy is accompanied by the growth of unit capacities of generators of wind power plants. The paper analyzes the efficiency of a wind power plant based on modern wind generators for predetermined location conditions, taking into account operating costs based on operational experience and based on the assessment of the power plant’s participation in the balancing market of electricity with a waiver of the "green tariff". Calculations of the technical and economic indicators of an imaginary designed 4-unit wind power plant with various wind generators under the wind conditions of a predetermined industrial site located in the Carpathian region of Ukraine were carried out. The calculations take into account the modern typical characteristics of wind generators, additional operating costs and the estimated cost of electricity purchase of the station under the "green tariff" and in the conditions of a balancing electricity market to compare economic efficiency. In order to make an optimal design technical decision with a comparative assessment, three types of wind generators were determined for installation at an imaginary wind farm - Enercon E-175 EP5, Vestas V136-4.5 MW and Vestas V172-7.2 MW. In the conditions of the predetermined construction site of the projected wind farm on the Carpathian ridges of Ukraine, the measured and calculated annual probability distribution of wind speed according to the analytical Weibull distribution is applied, and the characteristics of the annual productivity of the 4-unit wind farm for the adopted three types of wind generators are given. The technical and economic characteristics were obtained in the work: capital investment, operating costs, characteristics of electricity production, the gross profit during the annual operation of the wind power plant with three options for installing wind generators was calculated, making it possible to estimate the payback time of the investment in the construction of the wind plant. So, for a 4-unit station with generators of the Enercon E-175 EP5, the payback period is 3.3 years, and with wind generators of the Vestas V136-4.5 MW - 3.4 years, as well as for the Vestas V172-7.2 MW in operating conditions of the "green tariff" and, respectively, 2.9 years, 2.9 years and 3.0 years under conditions of sale of electricity at balancing market prices. Additional operating costs for the disposal of worn wind turbine blades do not have a significant impact on the overall cost indicators and amount to 5-7% of the total costs. Key words: wind power plant, wind generators, real wind conditions, performance characteristics, payback period